Public Spitting During Pandemic Times in India. (15th September 2021) - Saha, Ria; Keshri, Vikash R.; Chauhan, Bal Govind; Jungari, Suresh
Traditionally the act of public spitting has been a putative "socio-cultural problem" in India. With the growing intensity of COVID-19 pandemic in India, it is of a predominant public health concern as evidence indicates sputum to be the potential reservoir of COVID-19 virus particles which could be easily transmitted. Despite being a significant public health issue, which is also linked to several other communicable diseases most notably tuberculosis (apart from COVID-19), this indiscriminate behavior has not received the due policy attention warranted. National and sub-national government enforcements and community level mass prudence to control this issue have been significantly dismal. Therefore, we aim to propose policy recommendations for short-term and long-term actions to prioritize this issue. The commentary advocates for immediate attention from national level policymakers and public health agencies to collectively respond to this issue and prevent (mitigate) any additional public health sufferings arising from this. Keywords: Public spitting, COVID-19, transmission, policy, India, smokeless tobacco.